Sector studies : Suriname : rural sector note (FAO RomeIT, 2005)
Seeks to update available knowledge on the sector and eventually serve as a basis of further discussions between the government and the World Bank on programmes and projects of mutual interest for follow-up.
Keywords: RURAL DEVELOPMENT